The Effect of Organizational Commitment and Personal Costs on Intention to do Whistleblowing - Pratiwi, Yunita; Rahayu, Sri; Yetti, Susfa (International Journal of Multidisciplinary Approach Research and Science, 2023)
This research was conducted to examine the causes or factors that influence a person's intention to do whistleblowing. This study aims to determine whether Organizational Commitment and Personal Cost affect the intention to do whistleblowing at the Jambi Province Education Office. The data used is primary data obtained through questionnaires distributed to employees who work at the Jambi Province Education Office and the research sample is 268 employees who work at the Jambi Provincial Education Office with a sampling technique using saturated sampling method. Methods of data analysis using multiple linear regression analysis using the SPSS program.